Market Facilitation Program Payments, Employer-Sponsored Health Insurance Coverage and Off-Farm Employment - Ashok K. Mishra; Alexis H. Villacis; Cristina D. M. Miller (Institute of Labor Economics (IZA), 2022)
About two-thirds of U.S. farm households are employed off the farm. Off-farm sources represent 85 percent of the income earned by the average farm household and have turned into their main source of health insurance coverage. Farmers receive various government farm program payments, including the recently added Market Facilitation Program (MFP) payments. These payments have an unintended consequence on labor supply by farm operator households. Using farm household-level data from the 2019 Agricultural Resource Management Survey, this study investigates the impact of employer-sponsored health insurance coverage and participation in MFP on off-farm labor allocation decisions of U.S. farm families. Results from our empirical model show that farm families are 52% more likely to work off the farm if off-farm jobs provide employer-sponsored health insurance coverage. More importantly, results show that MFP payments have a significant and negative effect on the off-farm employment of U.S. farm-operator households.
Keywords: C34; I13; J22; J38; J43; Q12; Q18; 330; Agricultural Resource Management Survey; government subsidies; employer-sponsored health insurance coverage; off-farm employment